2017
DOI: 10.1111/aab.12342
|View full text |Cite
|
Sign up to set email alerts
|

Development, histological observations and Grapevine leafroll‐associated virus‐3 localisation in in vitro grapevine micrografts

Abstract: Development, histological process and Grapevine leafroll-associated virus-3 localisation were studied in micrografts of three scion/rootstock combinations: healthy/healthy, healthy/infected and infected/healthy. Earlier bud break and faster growth in scions of micrografts were obtained when the healthy shoot segments were used as scions, while earlier bud break in rootstocks and greater fresh weight of roots in micrografts were produced when the healthy shoot segments were used as rootstocks. All histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 59 publications
2
19
0
Order By: Relevance
“…The combination of GLRaV‐1 and GVA, however, was more detrimental than sole infection with GLRaV‐1. Callus formation between the surfaces of scion and rootstock has been found 3 days after micrografting in other studies (Ribeiro et al , Hao et al ). We did not check the healing status of the graft union that early, but our results showed that clear and dense callus tissues were already visible in LR131 graft unions 7 days after grafting.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…The combination of GLRaV‐1 and GVA, however, was more detrimental than sole infection with GLRaV‐1. Callus formation between the surfaces of scion and rootstock has been found 3 days after micrografting in other studies (Ribeiro et al , Hao et al ). We did not check the healing status of the graft union that early, but our results showed that clear and dense callus tissues were already visible in LR131 graft unions 7 days after grafting.…”
Section: Discussionmentioning
confidence: 55%
“…Our histological observation showed that LR131 did not have a significant impact on the healing of graft unions in the period of time evaluated, but LR132 appeared to prevent the healing process, causing the death of all the micrografts. Hao et al () found that GLRaV‐3 did not affect the healing process of Cabernet Sauvignon auto‐grafts, either. The combination of GLRaV‐1 and GVA, however, was more detrimental than sole infection with GLRaV‐1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations